Applying of pollution indices as a monitoring tool for assessment of water quality in Tigris River, Baiji district, Salah alden governorate - Mahmood Fadhil Abed; Salwa Hadi Ahmed (Tikrit Journal of Pure Science)
This research has investigated the quality of surface water at Baiji district of Salah Alden governorate based on 5 sampling stations for two season (September 2012 and April 2013). Water evaluation indices (i.e. heavy metal pollution index (HPI), heavy metal evaluation index (HEI) and contamination degree index (Cd)) are utilized to characterize the quality of water in term of drinking purposes. All values of HPI were lower than (15), suggesting low heavy metal pollution. The values of HEI were also less than (10), indicating low heavy metal pollution, whereas Cd values were much less than (1) for all stations, indicating low heavy metal pollution. Consequently, Tigris River water in the study area is suitable for drinking purposes in terms of heavy metal pollution.